2010
DOI: 10.1111/j.1460-9592.2010.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural clonidine on minimum local anesthetic concentration (ED50) of levobupivacaine for caudal block in children

Abstract: Clonidine produces a local anesthetic sparing effect with a dose-dependent decrease in levobupivacaine MLAC for caudal anesthesia. In addition, there is a dose-dependent prolongation of postoperative analgesia following lower abdominal surgery in children. A dose of 2 μg·kg(-1) of clonidine provides the optimum balance between improved analgesia and minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
(58 reference statements)
2
27
3
Order By: Relevance
“…15 As an oral premedicant, higher doses of clonidine (4lg/kg) were associated with less postoperative nausea and vomiting after surgery for strabismus. 16 For SEMLS, multiple dermatomes (L1-S2) must be blocked to attain satisfactory epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As an oral premedicant, higher doses of clonidine (4lg/kg) were associated with less postoperative nausea and vomiting after surgery for strabismus. 16 For SEMLS, multiple dermatomes (L1-S2) must be blocked to attain satisfactory epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 The minimum local anaesthetic concentration of levobupivacaine for caudal epidural block in children decreases in a dose-dependent manner and the duration of effect prolonged, with increasing dose of added clonidine. 15 As an oral premedicant, higher doses of clonidine (4lg/kg) were associated with less postoperative nausea and vomiting after surgery for strabismus. 16 For SEMLS, multiple dermatomes (L1-S2) must be blocked to attain satisfactory epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Gupta also showed a significant prolongation of duration of analgesia in their respective studies when clonidine was used as an adjuvant to local anaesthetics in epidural administration. Disma N et al 19 showed that a dose of 2μg/kg of clonidine increases the duration of post-operative analgesia in caudal anaesthesia for lower abdominal surgery. Clonidine produces analgesia by blocking the conduction of C and Aδ fibers and increasing potassium conductance in isolated neurons in vitro and thereby intensifying conduction block of local anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…While the clonidine group showed a greater fall in systolic and diastolic blood pressure compared to the control group this change was statistically insignificant. Similarly the studies conducted by Ghatak T et al 19 and Alves TCA and Braz JRC 17 showed no significant decrease in blood pressure between the clonidine and the control groups in their respective studies.…”
mentioning
confidence: 89%
“…In addition, there was a dose dependent prolongation of postoperative analgesia following lower abdominal surgery in children. A dose of 2 µg kg of clonidine provides the optimum balance between improved analgesia and minimal side effects [10] .…”
Section: Discussionmentioning
confidence: 99%